2015
DOI: 10.4103/0976-9668.149119
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and protective effects of Phytoceeagainst carbon tetrachloride-induced oxidative stress

Abstract: Background:This study evaluated the antioxidant potential of a polyherbal formulation (Phytocee™) in the rodent model.Materials and Methods:Four groups of rats (n = 6) were pretreated with Vitamin C (20 mg/kg) or Phytocee™ (20, 100, and 200 mg/kg), respectively for 10 days. Oxidative stress in rat liver was induced by administration of carbon tetrachloride (CCl4) at 2 ml/kg as a single dose orally to all groups except the vehicle control group. After 24 h of administration of CCl4, hepatic levels of malondiald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Higher levels of corticosterone lead to increase in oxidative stress, decrease in follicle numbers, induce cell death in follicular cells and subsequently reducing egg production [17]. Reference [9] reported that PGC had markedly reversed induced oxidative stress and can be used as an antioxidant feed supplement. The herbs present in the PGC are known to have antioxidant, antistress, adaptogenic, immunomodulatory properties.…”
Section: A Effect Of Pgc On Egg Production and Feed Intake Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of corticosterone lead to increase in oxidative stress, decrease in follicle numbers, induce cell death in follicular cells and subsequently reducing egg production [17]. Reference [9] reported that PGC had markedly reversed induced oxidative stress and can be used as an antioxidant feed supplement. The herbs present in the PGC are known to have antioxidant, antistress, adaptogenic, immunomodulatory properties.…”
Section: A Effect Of Pgc On Egg Production and Feed Intake Parametersmentioning
confidence: 99%
“…PGC contains active phytochemicals like polyphenols, withanolides and other triterpenoids. Some studies already showed that PGC is a natural defense enhancer which boosts endurance, optimizes cell mediated immunity as well as helps in reducing harmful effects of stress [9], [10]. In addition, these individual plant ingredients have shown antioxidant property, and as a whole many studies have shown the effectiveness of PGC in in vitro and invivo models combating stress [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance between the generation of ROS and cellular antioxidant capacity can lead to oxidative stress. [ 1 2 ] ROS are implicated in the etiology of several degenerative diseases such as stroke, rheumatoid arthritis, diabetes mellitus, peptic ulcer, and cancer. [ 3 4 ] Phytomedicine plays a very important role in the management of most of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Even though proofs of efficacy on these PFS are available [ 5 , 6 ], it is vital to assess safety to support their long-term use. Hence, the current study evaluated the PFS for their possible toxic potential by using in vitro BRMT and in vivo acute oral toxicity test.…”
Section: Introductionmentioning
confidence: 99%